Uncovering the Natural History of the Bromeligenous Frog Crossodactylodes izecksohni (Leptodactylidae, Paratelmatobiinae) - Ferreira, Rodrigo B.; Monico, Alexander T.; Zocca, Cassio Z.; Santos, Marcus Thadeu T. [UNESP]; Lirio, Fernanda C. F.; Tonini, Joao F. R.; Sabagh, Leandro T.; Cipriano, Rafael S.; Waichert, Cecilia; Crump, Martha L.; Beard, Karen H.; Toledo, Luis Felipe; et al. (Soc Brasileira Herpetologia, 2019)
Leptodactylidae consists of more than 200 described species distributed throughout the Neotropics. The five species in the genus Crossodactylodes are the only species in this family that complete their entire life cycle in rainwater accumulated between bromeliad leaves. We surveyed bromeliads for Crossodactylodes izecksohni in its type locality: the municipality of Santa Teresa, Brazil's Atlantic Forest. We found C. izecksohni in 12 species of bromeliads. The sex ratio was approximately 1:1. Males were distinguished from females by hypertrophy of upper and forearms and the presence of nuptial pads formed by well-developed spines on the first finger. Eggs, tadpoles, juveniles, and adults were found in bromeliads throughout the year. Males defended clusters of a few bromeliads. Females were also territorial. Female choice was the main mate acquisition tactic of C. izecksohni, but male-male competition and satellite strategy were displayed as well. Males also called from axils with eggs and tadpoles. The clutch structure was a single egg either aquatic-free or non pendant, slightly suspended above the water level, and attached to a bromeliad leaf. The mean number of eggs and tadpoles found in occupied bromeliads was 2.5 (range 1-7) and 3.5 (range 1-10), respectively. Males guarded and defended eggs and tadpoles against conspecilics and predators. Adults displayed a wide variety of antipredator mechanisms. Limited resources within bromeliads may drive selective pressure and result in the deposition of few large eggs, parental care behaviors, and territoriality. The complex behavior of C. izecksohni makes it a model taxon for the study of behavioral and evolutionary ecology.
Keywords: Aggressive behavior; Antipredator mechanism; Atlantic Forest; Parental care; Reproduction; Territoriality; Vocalization